Protein Secondary Structure Affects Glycan Clustering in Native Mass Spectrometry - Hao Yan; Julia Lockhauserbäumer; Gergo Peter Szekeres; Alvaro Mallagaray; Robert Creutznacher; Stefan Taube; Thomas Peters; Kevin Pagel; Charlotte Uetrecht (Life, 2021)
Infection by the human noroviruses (hNoV), for the vast majority of strains, requires attachment of the viral capsid to histo blood group antigens (HBGAs). The HBGA-binding pocket is formed by dimers of the protruding domain (P dimers) of the capsid protein VP1. Several studies have focused on HBGA binding to P dimers, reporting binding affinities and stoichiometries. However, nuclear magnetic resonance spectroscopy (NMR) and native mass spectrometry (MS) analyses yielded incongruent dissociation constants (KD) for the binding of HBGAs to P dimers and, in some cases, disagreed on whether glycans bind at all. We hypothesized that glycan clustering during electrospray ionization in native MS critically depends on the physicochemical properties of the protein studied. It follows that the choice of a reference protein is crucial. We analysed carbohydrate clustering using various P dimers and eight non-glycan binding proteins serving as possible references. Data from native and ion mobility MS indicate that the mass fraction of β-sheets has a strong influence on the degree of glycan clustering. Therefore, the determination of specific glycan binding affinities from native MS must be interpreted cautiously.